ANALYSIS OF MATHEMATICAL PROBLEM-SOLVING SKILLS OF INDONESIAN HIGH SCHOOL STUDENTS OF LINEAR PROGRAMME MATERIAL - Fitriani , Indah (Prodi Administrasi Pendidikan Program Pascasarjana Universitas Riau, 2025)
Mathematical Problem-Solving Ability is an important competency that students must have in the process of learning mathematics. KPMM is a crucial aspect because it can help students in solving various problems faced, both inside and outside the learning context. This study aims to describe students' KPMM, especially in linear programme material, using a descriptive approach. The subjects in this study were 23 students of class XI Accounting of SMK Keuangan Pekanbaru in the academic year 2024/2025. The instrument used was a written test consisting of two items and four indicators of KPMM that refer to the steps of problem solving according to Polya. The results showed that in the indicator of understanding the problem, the average student achievement was 47.10% and was in the insufficient category. In the indicator of planning the solution, the average achievement was 75% in the good category. The indicator of implementing the solution plan obtained an average of 65.94% and was included in the sufficient category. Meanwhile, the indicator of rechecking showed the lowest achievement with an average of 51.09% which was included in the very poor category. Overall, the average KPMM of students is 59.78% which is in the sufficient category. Based on these findings, it is suggested that students should be given more practice with non-routine problems to improve their overall mathematical problem-solving skills.